Behind the Scenes : The politics of planning Adelaide - Llewellyn-Smith, Michael (University of Adelaide Press, 2012)
Behind the Scenes examines planning in the City of Adelaide from 1972 until 1993 within the historical framework of City/State relations from 1836 when the Province of South Australia was founded. During this 21-year period, the City had its own planning and development control legislation separate from the rest of the State. Dr Llewellyn-Smith examines why this situation came about, why it continued for this particular period and why it ceased in 1993 when the separate legislation was repealed and the City became part of the State system under the new Development Act 1993. Behind the Scenes includes original interviews with many of the key individuals in the City and State who played influential roles during this period. Dr Llewellyn-Smith himself was the City Planner from 1974 until 1981 and then the Town Clerk/Chief Executive Officer of the Adelaide City Council from 1982 until 1993: this book, then, is both a work of scholarship and an insider's account.
Keywords: City Development; City Planning; History; Politics; Sydney City Council